HEART AND AGE (PART III): MODIFYING AGEING PROCESSES - D. U. Akasheva; E. V. Plokhova; I. D. Strazhesko; E. N. Dudinskaya; O. N. Tkacheva (Кардиоваскулярная терапия и профилактика, 2013)
The share of elderly people in the general population has been steadily increasing. Age is one of the main risk factors (RFs) of cardiovascular disease. However, the current focus of preventive medicine is on modifiable RFs, such as arterial hypertension, hypercholesterolemia, and smoking, while age is regarded as a nonmodifiable, non-correctable RF. This emphasises the importance of the identification of cardiac ageing mechanisms and potential modifying interventions. All the existing methods which target cardiac ageing processes have not been used in the clinical settings and require further research. The key intervention methods are described in the paper.